A fluorine-free flame-retardant PC material and preparation method thereof

By combining fluorine-free flame retardant and silicon PC, PC materials with good flame retardant properties, anti-aging properties and high light transmittance are prepared, which solves the problem of light transmittance and physical performance reduction caused by the improvement of flame retardant properties in the prior art, and avoids the potential harm of fluorine-containing flame retardant to the environment.

CN118931150BActive Publication Date: 2025-04-08DONGGUAN GUOHENG PLASTIC TECH CO LTD

Patent Information

Application Number
CN202411256578.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-04-08
Estimated Expiration
2044-09-09

AI Technical Summary

Technical Problem

When existing PC materials improve flame retardant properties and anti-aging properties, they are prone to decrease light transmittance and physical properties, and fluorine-containing flame retardants may release harmful fluoride during combustion, causing potential harm to human health and the environment.

Method used

Fluorine-free flame retardant is used, consisting of polydiphenyloxyphosphazene, tetraphenylbisphenol A diphosphate, polydimethylsiloxane, methacrylate-based phenyl polymer composite, etc., combined with silicon PC, it is prepared through melt extrusion and granulation processes to ensure the transparency and flame retardant properties of the material.

Benefits of technology

It achieves good flame retardant properties and anti-aging properties of PC materials, while maintaining high light transmittance and physical properties, reducing potential harm to human health and the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005034278740000051
    Figure BDA0005034278740000051
  • Figure BDA0005034278740000061
    Figure BDA0005034278740000061
  • Figure BDA0005034278740000071
    Figure BDA0005034278740000071
Patent Text Reader

Abstract

The present application relates to the field of polymer composite materials, and more specifically, it relates to a fluorine-free flame retardant PC material and a preparation method thereof, which is composed of the following raw materials in weight percentage: 10-15% silicon PC, 0.1-1% anti-aging agent, 2-6% fluorine-free flame retardant, and the balance is PC; the fluorine-free flame retardant is composed of at least three of polydiphenyloxyphosphazene, tetraphenyl bisphenol A diphosphate, polydimethylsiloxane, and methacrylate-based phenyl polymer complex. When polydiphenyloxyphosphazene, tetraphenyl bisphenol A diphosphate, polydimethylsiloxane, and methacrylate-based phenyl polymer complex are compounded, a synergistic effect is achieved, and the silicon PC is combined to make the prepared PC material have better flame retardant properties, light transmittance, anti-aging properties, and physical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of polymer composite materials, and more specifically, to a fluorine-free flame-retardant PC material and a preparation method thereof. Background Art

[0002] PC material has high transparency, impact resistance, heat resistance, high strength, UV resistance, weather resistance, fatigue resistance, etc. Therefore, it is often used in machinery and equipment, automobile industry, construction industry, textile industry, daily necessities, etc. For example, it is used in sunlight panels and sunlight boron, which has a better light transmission effect.

[0003] Sun panels and solar panels are usually installed outdoors. In hot and dry seasons, they are prone to fire. In order to avoid the hidden danger of fire in sun panels and solar panels, flame retardants are usually added to improve the flame retardant properties of PC materials. However, commonly used flame retardants are magnesium hydroxide, aluminum hydroxide, etc. When using the above flame retardants, they need to be added in large amounts to achieve better flame retardant effects. Large amounts added will also significantly reduce the physical properties and light transmittance of PC materials.

[0004] In response to the above problems, fluorinated flame retardants such as potassium fluorinated benzenesulfonylbenzenesulfonate, potassium perfluorobutylsulfonate, fluorinated phosphate esters, and fluorinated styrene glycol are currently used. They have the advantages of good flame retardant effect, small addition amount, good heat resistance, and anti-aging performance. Therefore, the addition of fluorinated flame retardants has little effect on the physical properties and light transmittance of PC materials, and can further improve the anti-aging performance of PC materials.

[0005] Although fluorinated flame retardants have significant effects in improving the flame retardancy and anti-aging properties of materials, and will not significantly reduce the light transmittance and physical properties of PC materials, fluorinated compounds may release harmful fluorides during combustion, causing potential harm to human health and the environment. Therefore, further research on flame-retardant PC materials is needed. Summary of the invention

[0006] In order to obtain better flame retardant properties, light transmittance, anti-aging properties and physical properties, the present application provides a fluorine-free flame retardant PC material and a preparation method thereof.

[0007] In the first aspect, the present application provides a fluorine-free flame retardant PC material, which is composed of the following raw materials in percentage by weight: PC 65-83%

[0008] Silicon PC 10-15%

[0009] Anti-aging agent 0.1-3%

[0010] Fluorine-free flame retardant 5-20%;

[0011] The fluorine-free flame retardant is composed of at least three of polydiphenyloxyphosphazene, tetraphenyl bisphenol A diphosphate, polydimethylsiloxane, and methacrylate-based phenyl polymer compound.

[0012] In the above technical solution, silicon PC is a material that improves the performance of polycarbonate by introducing an organic silicon structure. Silicon PC combines the transparency and impact resistance of PC with the flame retardant, heat resistant and antioxidant properties of organic silicon. After compounding, it can generate an inorganic oxygen-insulating and heat-insulating protective layer containing Si bonds and (or) Si-C bonds during combustion, effectively preventing the escape of combustion decomposition products and inhibiting the thermal decomposition of polymer materials, achieving flame retardant, low smoke and low toxicity effects, while maintaining the transparency of PC materials and further improving the physical properties, anti-aging properties and flame retardant properties of PC materials.

[0013] Polydiphenyloxyphosphazene, tetraphenyl bisphenol A diphosphate, polydimethylsiloxane, and methacrylate-based phenyl polymer compounds all have the advantages of being fluorine-free, transparent, and flame-retardant. When three of them are compounded, they can have a better synergistic effect, and combined with silicon PC, the resulting PC material has the characteristics of being fluorine-free, flame-retardant, transparent, and impact-resistant.

[0014] Polydimethylsiloxane has excellent light transmittance, with a light transmittance of up to 100%. It also has high flame retardancy and flexibility. The silicon-oxygen bonds form a protective layer when heated, isolating oxygen and heat, thereby improving the flame retardancy of the material.

[0015] The methacrylate-based phenyl polymer complex contains methacrylate groups and phenyl groups, so it has better heat resistance, anti-aging and optical properties, and can also play the role of flame retardancy and enhancement of physical properties. When it is compounded with polydiphenyloxyphosphazene, tetraphenyl bisphenol A diphosphate, and polydimethylsiloxane, it has a better synergistic effect. The obtained fluorine-free flame retardant and silicon PC have a synergistic flame retardant effect, so that the obtained PC material has better flame retardancy, anti-aging, light transmittance and physical properties.

[0016] In summary, when polydiphenyloxyphosphazene, tetraphenyl bisphenol A diphosphate, polydimethylsiloxane, and methacrylate-based phenyl polymer complex are compounded, they play a synergistic role, and when combined with silicon PC, the PC material has better anti-aging and flame retardant properties, and maintains better light transmittance and physical properties. When used in sun panels, sun sheds, etc., it plays a better role in anti-aging, flame retardant, light transmission, damage resistance, etc., and improves its durability and safety performance.

[0017] Preferably, the fluorine-free flame retardant is composed of polydiphenyloxyphosphazene, tetraphenyl bisphenol A diphosphate, polydimethylsiloxane, and methacrylate-based phenyl polymer composite in a weight ratio of (1-4):1:(1-2):(6-8).

[0018] When the polydiphenyloxyphosphazene, tetraphenyl bisphenol A diphosphate, polydimethylsiloxane, and methacrylate-based phenyl polymer composite are used, a better synergistic effect is achieved, the flame retardant properties, anti-aging properties, and physical properties of the PC material are further improved, and a better light transmittance is maintained.

[0019] Preferably, the methacrylate-based phenyl polymer compound is composed of the following raw materials in percentage by weight:

[0020] Polysiloxane-acrylate copolymer 8-15%

[0021] Phenyl phenoxyethyl acrylate 18-30%

[0022] Toughener 5-10%

[0023] The balance is methacrylate mono-terminated dimethylpolysiloxane;

[0024] The total weight percentage of the polysiloxane-acrylate copolymer, phenylphenoxyethyl acrylate, toughening agent, and methacrylate mono-terminated dimethylpolysiloxane is 100%.

[0025] Methacrylate mono-terminated dimethylpolysiloxane and polysiloxane-acrylate copolymers combine the properties of silicone and acrylate, and have excellent optical, anti-aging and flame retardant properties; phenylphenoxyethyl acrylate has a high light transmittance and contains a benzene ring, which improves the heat resistance and anti-aging properties of the material, and contains acrylate reactive groups. The toughening agent plays a role in toughening PC, while promoting the mixing of methacrylate-based phenyl polymer complexes with PC, silicon PC, polydiphenyloxyphosphazene, tetraphenyl bisphenol A diphosphate, polydimethylsiloxane and other raw materials, so that the PC material raw material system is fully mixed and uniform, further improving the flame retardant and physical properties of PC materials, and maintaining good light transmittance and anti-aging properties.

[0026] Methacrylate mono-terminated dimethyl polysiloxane has one or both ends of its molecular chain terminated by methacrylate groups, and can be copolymerized or grafted with other monomers or polymers containing double bonds through free radical polymerization; and then compounded with polysiloxane-acrylate copolymer, phenylphenoxyethyl acrylate, and toughening agent, and blended with the assistance of initiator and solvent, the obtained methacrylate-based phenyl polymer composite has better flame retardant, light transmission, anti-aging and toughening effects. When it is compounded with polydiphenyloxyphosphazene, tetraphenyl bisphenol A diphosphate, and polydimethylsiloxane, and then interacts with silicon PC, the obtained PC material has better comprehensive performance.

[0027] Usually, the light transmittance of sun panels and sun sheds is above 85%. The light transmittance of the PC material after adding flame retardant in this application is also above 85%, and it also has better flame retardant performance, anti-aging performance and physical properties. It improves the durability and safety performance of sun panels and sun sheds.

[0028] Preferably, the polysiloxane-acrylate copolymer is polydimethylsiloxane-poly 6-4-cyanobiphenyl-4-oxy-hexyl methacrylate and / or acrylic-cage polysilsesquioxane.

[0029] Polydimethylsiloxane-poly 6-4-cyanobiphenyl-4-oxy-methacrylate hexyl or acrylic acid-cage polysilsesquioxane both have good flame retardant effect and optical properties. The acrylic acid group contained in it can be blended with polysiloxane-acrylate copolymer and phenylphenoxyethyl acrylate in one step, and then combined with toughening agent, so that the prepared methacrylate-based phenyl polymer compound has good optical, physical, anti-aging, flame retardant and other properties. And after compounding with polydiphenyloxyphosphazene, tetraphenyl bisphenol A diphosphate, polydimethylsiloxane, and silicon PC, it has a good synergistic effect, so that the PC material has better comprehensive performance.

[0030] When polydimethylsiloxane-poly 6-4-cyanobiphenyl-4-oxy-hexyl methacrylate and acrylic-cage polysilsesquioxane are compounded, a synergistic effect is achieved, so that the flame retardant, anti-aging, physical and other properties of the PC material are better, and better light transmittance is maintained.

[0031] Preferably, the phenylphenoxyethyl acrylate is o-phenylphenoxyethyl acrylate and / or 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene.

[0032] The o-phenylphenoxyethyl acrylate and 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene are colorless in appearance and have good optical properties. The phenyl group can improve the flame retardancy, heat resistance and anti-aging properties. The acrylate group contained in the methacrylate is further blended with methacrylate mono-terminated dimethylpolysiloxane and polysiloxane-acrylate copolymer to make the prepared methacrylate-based phenyl polymer composite have better comprehensive properties.

[0033] Preferably, the weight ratio of the o-phenylphenoxyethyl acrylate and / or 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene is (1-3):1.

[0034] When the present application uses o-phenylphenoxyethyl acrylate and / or 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene for compounding, a synergistic effect is achieved, thereby enabling the methacrylate-based phenyl polymer composite to obtain better comprehensive performance.

[0035] Preferably, the toughening agent is polyethylene oxide-polypropylene oxide-polyethylene oxide block copolymer and / or polystyrene-hydroxy-poly(1,4-isoprene).

[0036] Polyethylene oxide-polypropylene oxide-polyethylene oxide block copolymer and / or polystyrene-hydroxy-poly(1,4-isoprene) have better toughening effect and can promote the compatibility of methacrylate-based phenyl polymer composite with other materials, so that the obtained PC material has better comprehensive performance.

[0037] Preferably, the methacrylate-based phenyl polymer complex is prepared by the following method:

[0038] According to parts by weight, polysiloxane-acrylate copolymer, phenylphenoxyethyl acrylate, toughening agent, and methacrylate mono-terminated dimethylpolysiloxane are weighed and mixed, and a solvent and an initiator are added to mix them thoroughly and evenly, and then reacted. After the reaction is completed, the solvent is removed, and the mixture is dried and crushed to obtain a methacrylate-based phenyl polymer composite.

[0039] In the above scheme, polysiloxane-acrylate copolymer, phenylphenoxyethyl acrylate, toughening agent, initiator, and methacrylate mono-terminated dimethylpolysiloxane are dissolved in a solvent, mixed evenly, and heated to allow them to blend and react under the auxiliary action of the initiator and the solvent. After removing the solvent, drying, and crushing, the obtained methacrylate-based phenyl polymer composite has better optical, flame retardant, antioxidant, and toughening effects. When it is used in the PC material raw material system, it works together with polydiphenyloxyphosphazene, tetraphenyl bisphenol A diphosphate, polydimethylsiloxane, and silicon PC to play a synergistic role, thereby enabling the PC material to obtain better light transmission performance, flame retardant performance, physical properties, and anti-aging performance. When used in sun sheds or sun panels, it has better durability and safety performance.

[0040] In a second aspect, the present application provides a method for preparing a fluorine-free flame-retardant PC material, which is obtained by the following method:

[0041] According to the weight, PC, silicon PC, anti-aging agent and fluorine-free flame retardant are weighed and mixed evenly, melt-extruded, cooled, dried and granulated to obtain fluorine-free flame retardant PC material.

[0042] Through the above process, the materials are fully mixed and uniformly mixed. After melt extrusion, cooling, drying and granulation, the obtained fluorine-free flame retardant PC material has better flame retardant performance and anti-aging performance, while maintaining better physical properties and light transmittance.

[0043] In summary, this application has the following beneficial effects:

[0044] 1. When polydiphenyloxyphosphazene, tetraphenyl bisphenol A diphosphate, polydimethylsiloxane, methacrylate phenyl polymer compound and more than three kinds are compounded, they play a synergistic role, and with silicon PC, the PC material has better anti-aging and flame retardant properties, and maintains better light transmittance and physical properties. When it is used in automobile lights, lenses, sun panels, sun sheds, etc., it plays a better role in anti-aging, flame retardant, light transmission, damage resistance, etc., and improves its durability and safety performance.

[0045] 2. After compounding methacrylate mono-terminated dimethylpolysiloxane with polysiloxane-acrylate copolymer, phenylphenoxyethyl acrylate, and toughening agent, with the assistance of initiator and solvent, the obtained methacrylate-based phenyl polymer composite has better flame retardant, light transmittance, anti-aging and toughening effects. When it is compounded with polydiphenyloxyphosphazene, tetraphenyl bisphenol A diphosphate, and polydimethylsiloxane, and then interacts with silicon PC, the obtained PC material has better comprehensive performance. DETAILED DESCRIPTION

[0046] The present application is further described in detail below with reference to the embodiments.

[0047] Introduction of some raw materials;

[0048] Table 1 Introduction of some raw materials

[0049]

[0050]

[0051] Preparation Example of Methacrylate-Based Phenyl Polymer Complex

[0052] Preparation Example 1

[0053] The methacrylate-based phenyl polymer complex was prepared by the following method:

[0054] According to weight percentage, 8% polysiloxane-acrylate copolymer, 30% phenylphenoxyethyl acrylate, 5% toughening agent, 57% methacrylate mono-terminated dimethylpolysiloxane and appropriate amounts of initiator and solvent (the initiator and the solvent are 1% and 200% of the total weight of polysiloxane-acrylate copolymer, phenylphenoxyethyl acrylate, toughening agent and methacrylate mono-terminated dimethylpolysiloxane, respectively) are weighed, mixed and put into a reaction kettle, mixed evenly, heated to 56°C under nitrogen protection, reacted for 2h, then heated to 120°C, and distilled under reduced pressure. The vacuum gauge showed 0.08MPa, and the solvent was completely removed to obtain a methacrylate-based phenyl polymer composite.

[0055] The polysiloxane-acrylate copolymer is polydimethylsiloxane-poly 6-4-cyanobiphenyl-4-oxy-hexyl methacrylate; the phenylphenoxyethyl acrylate is o-phenylphenoxyethyl acrylate; the toughening agent is polyethylene oxide-polypropylene oxide-polyethylene oxide block copolymer; the initiator is diisopropyl peroxydicarbonate, and the solvent is ethyl acetate.

[0056] Preparation Example 2-3

[0057] The difference between Preparation Example 2-3 and Preparation Example 1 is that the amount of raw materials and process parameters are different, as shown in Table 2;

[0058] Table 2 Raw material dosage of preparation examples 1-3 (%)

[0059]

[0060] Preparation Example 4

[0061] The difference between Preparation Example 4 and Preparation Example 2 is that the polysiloxane-acrylate copolymer is composed of polydimethylsiloxane-poly 6-4-cyanobiphenyl-4-oxy-methacrylate and acrylic acid-cage polysilsesquioxane in a weight ratio of 1:1.

[0062] Preparation Example 5

[0063] Preparation Example 5 is different from Preparation Example 4 in that phenylphenoxyethyl acrylate is composed of o-phenylphenoxyethyl acrylate and 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene in a weight ratio of 2:1.

[0064] Preparation Example 6

[0065] The difference between Preparation Example 6 and Preparation Example 5 is that the toughening agent is composed of polyethylene oxide-polypropylene oxide-polyethylene oxide block copolymer and polystyrene-hydroxy-poly(1,4-isoprene) in a weight ratio of 4:1.

[0066] Preparation Comparative Example

[0067] Preparation Comparative Example 1

[0068] The difference between Preparation Comparative Example 1 and Preparation Example 1 is that the polysiloxane-acrylate copolymer is replaced by methacrylate mono-terminated dimethylpolysiloxane in an equal amount.

[0069] Preparation Comparative Example 2

[0070] The difference between Preparation Comparative Example 2 and Preparation Example 1 is that an equal amount of phenylphenoxyethyl acrylate is replaced by methacrylate mono-terminated dimethylpolysiloxane.

[0071] Preparation Comparative Example 3

[0072] The difference between Preparation Comparative Example 3 and Preparation Example 1 is that the toughening agent is replaced by methacrylate mono-terminated dimethyl polysiloxane in equal amount.

[0073] Example

[0074] Example 1

[0075] A fluorine-free flame retardant PC material is prepared by the following method:

[0076] According to weight percentage, 1% of polydiphenyloxyphosphazene, 0.5% of tetraphenyl bisphenol A diphosphate, and 0.5% of polydimethylsiloxane were weighed and mixed evenly to obtain a fluorine-free flame retardant.

[0077] Weigh 82% PC, 15% silicone PC, 1% anti-aging agent, and 2% fluorine-free flame retardant and add them into a mixing barrel. Start the agitator to stir the materials in the mixing barrel at a stirring rate of 100 r / min and a stirring time of 30 min. Then transfer them to a twin-screw extruder for melting and extrusion at a screw speed of 500 rpm. Cool them in a cold water tank, then enter an oven at 110°C for drying for 20 seconds, and then pass them into a granulator for granulation to obtain 20 kg of fluorine-free flame retardant PC material.

[0078] The temperature settings of the twin-screw extruder are as follows: zone 1 235°C, zone 2 245°C, zone 3 255°C, zone 4 270°C, zone 5 278°C, zone 6 260°C, zone 7 250°C, and die head 240°C.

[0079] The anti-aging agent is composed of an antioxidant 1010 and an ultraviolet absorber 234 in a weight ratio of 1:3.

[0080] Embodiment 2-5

[0081] The difference between Example 2-5 and Example 1 is that the composition of the raw materials and the same amount of the raw materials are different, as shown in Table 3;

[0082] Table 3 Composition of raw materials and the same amount of raw materials in Examples 1-5 (%)

[0083]

[0084] Embodiment 6-13

[0085] The difference between Examples 6-13 and Example 5 is that the sources of the methacrylate-based phenyl polymer complex are different, as shown in Table 4;

[0086] Table 4 Sources of methacrylate-based phenyl polymer complexes of Examples 6-13

[0087] Example Sources of Methacrylate-Based Phenyl Polymer Complexes Example 6 Preparation Example 2 Example 7 Preparation Example 3 Example 8 Preparation Example 4 Example 9 Preparation Example 5 Example 10 Preparation Example 6 Embodiment 11 Preparation Comparative Example 1 Example 12 Preparation Comparative Example 2 Embodiment 13 Preparation Comparative Example 3

[0088] Comparative Example

[0089] Comparative Example 1

[0090] The difference between Comparative Example 1 and Example 2 is that the fluorine-free flame retardant is replaced by silicon PC in equal amount.

[0091] Comparative Example 2

[0092] The difference between Comparative Example 2 and Example 2 is that an equal amount of silicon PC is replaced by PC.

[0093] Comparative Example 3

[0094] The difference between Comparative Example 3 and Example 2 is that polydimethylsiloxane is replaced by polydiphenyloxyphosphazene in equal amounts.

[0095] Comparative Example 4

[0096] The difference between Comparative Example 4 and Example 2 is that the fluorine-free flame retardant is aluminum hydroxide.

[0097] Performance testing

[0098] The fluorine-free flame-retardant PC materials obtained in Examples 1-13 and Comparative Examples 1-4 were injection molded to obtain test samples for the following experiments, which were then tested. The data are shown in Table 5.

[0099] Detection method / test method

[0100] Flame retardant performance: refer to ASTMD2863;

[0101] Notched impact toughness: refer to ASTM D256;

[0102] Light transmittance: Refer to GBT2410-2008 for light transmittance testing.

[0103] The specific data are shown in Table 5;

[0104] Table 5 Experimental data of Examples 1-13 and Comparative Examples 1-4

[0105]

[0106] Anti-aging performance: After the test samples obtained in Examples 1-13 and Comparative Examples 1-4 were aged, the transmittance was tested using the same testing method as in 1), and the residual transmittance was calculated (the residual transmittance refers to the transmittance obtained after the aging treatment divided by the transmittance obtained before the aging treatment, multiplied by 100%).

[0107] Aging treatment: Each cycle is 8 hours, a total of 72 cycles; the sample is placed in a closed experimental environment and irradiated with ultraviolet light for 7 hours (lamp UVA-340nm, power 0.63W / m 2 nm, temperature 80°C, humidity 60%), and then 1 hour of humidification (temperature 80°C, humidity 99%), each cycle test is continued until the test is completed.

[0108] Table 6 Experimental data of Examples 1-13 and Comparative Examples 1-4

[0109]

[0110]

[0111] Combining Example 2 and Comparative Examples 1-4 and Tables 5 and 6, it can be seen that the limiting oxygen index, notched impact toughness, and transmittance residual rate of Comparative Examples 1-4 are lower than those of Example 2, while the transmittance of Comparative Examples 1 and Comparative Examples 3-4 is lower than that of Example 2, and the transmittance of Comparative Example 2 is not significantly changed compared with that of Example 1, indicating that the raw material composition of the present application can obtain PC materials with better light transmittance, physical properties, flame retardant properties, and anti-aging properties.

[0112] By comparing Examples 4-10 with Example 2 and combining Tables 5 and 6, it can be seen that the limiting oxygen index, notched impact toughness, light transmittance, and light transmittance residual rate of Examples 4-10 are all higher than those of Example 2, indicating that the compounding of polydiphenyloxyphosphazene, tetraphenyl bisphenol A diphosphate, polydimethylsiloxane, and methacrylate-based phenyl polymer composite has a better synergistic effect, so that the PC material has better light transmittance, physical, flame retardant, anti-aging and other properties, so that it can be used in sunlight panels or sunlight boron, and has better flame retardant effect, light transmittance, durability and safety performance.

[0113] By comparing Examples 11-13 with Example 5 and combining Tables 5 and 6, it can be seen that the limiting oxygen index, notched impact toughness, transmittance, and transmittance residual rate of Examples 11-13 are all lower than those of Example 5, indicating that the methacrylate-based phenyl polymer composite prepared by using polysiloxane-acrylate copolymer, phenylphenoxyethyl acrylate, toughening agent, and methacrylate mono-terminated dimethyl polysiloxane, after compounding with polydiphenyloxyphosphazene, tetraphenyl bisphenol A diphosphate, and polydimethylsiloxane, and with silicon PC, has a synergistic effect, thereby obtaining a PC material with better anti-aging properties, physical properties, flame retardant properties, and optical properties.

[0114] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A fluorine-free flame-retardant PC material, characterized in that: It is composed of the following raw materials in weight percentage: Silicon PC10-15% Anti-aging agent 0.1-1% Fluorine-free flame retardant 2-6% The remainder is PC; The fluorine-free flame retardant is composed of polydiphenyloxyphosphazene, tetraphenyl bisphenol A diphosphate, polydimethylsiloxane, and methacrylate-based phenyl polymer composite in a weight ratio of (1-4): 1: (1-2): (6-8); The methacrylate-based phenyl polymer compound is prepared by including the following raw materials in weight percentage: Polysiloxane-acrylate copolymer 8-15% Phenyl phenoxyethyl acrylate 18-30% Toughener 5-10% The balance is methacrylate mono-terminated dimethylpolysiloxane; The total weight percentage of the polysiloxane-acrylate copolymer, phenylphenoxyethyl acrylate, toughening agent, and methacrylate mono-terminated dimethyl polysiloxane is 100%; The polysiloxane-acrylate copolymer is polydimethylsiloxane-poly 6-4-cyanobiphenyl-4-oxy-methacrylate hexyl and / or acrylic acid-cage polysilsesquioxane; The phenylphenoxyethyl acrylate is o-phenylphenoxyethyl acrylate and / or 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene; The toughening agent is polyethylene oxide-polypropylene oxide-polyethylene oxide block copolymer and / or polystyrene-hydroxy-poly(1,4-isoprene).

2. A fluorine-free flame-retardant PC material according to claim 1, characterized in that: The anti-aging agent is an antioxidant and / or an anti-UV agent.

3. The fluorine-free flame-retardant PC material according to claim 1, characterized in that: The weight ratio of the o-phenylphenoxyethyl acrylate to 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene is (1-3):

1.

4. A fluorine-free flame-retardant PC material according to claim 1, characterized in that: The methacrylate-based phenyl polymer complex is prepared by the following method: According to parts by weight, polysiloxane-acrylate copolymer, phenylphenoxyethyl acrylate, toughening agent, and methacrylate mono-terminated dimethylpolysiloxane are weighed and mixed, and a solvent and an initiator are added to mix them thoroughly and evenly, and then reacted. After the reaction is completed, the solvent is removed, and the mixture is dried and crushed to obtain a methacrylate-based phenyl polymer composite.

5. A method for preparing the fluorine-free flame-retardant PC material according to any one of claims 1 to 4, characterized in that: Obtained by the following method: According to the weight, PC, silicon PC, anti-aging agent and fluorine-free flame retardant are weighed and mixed evenly, melt-extruded, cooled, dried and granulated to obtain fluorine-free flame retardant PC material.

Citation Information

Patent Citations

  • Flame-retardant scratch-resistant polycarbonate composite material with low water absorption and preparing method thereof

    CN106147182A

  • High-transmittance thin-wall flame-retardant polycarbonate composition and preparation method thereof

    CN115850944A

Cited By

  • Needle-flame-resistant fluoride-free flame-retardant PC (polycarbonate) composite material as well as preparation method and application thereof

    CN121108709A

  • A needle flame-resistant fluorine-free flame-retardant PC composite material, a preparation method and application thereof

    CN121108709B